KESESUAIAN KOMPENSASI, KOMITMEN ORGANISASI, DAN BUDAYA ORGANISASI TERHADAP KEADILAN DISTRIBUTIF PADA PT. Z - Baggas Prasetyo; Setia Tjahyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine the effect of compensation suitability, organizational commitment and organizational culture on distributive justice. The object used is the company PT. Z. This study uses quantitative research methods. The population in this study were employees of PT. Z with a total of 58 employees, of which all existing employees are permanent employees. In this study, 49 permanent employees were used as samples with a sampling technique using non-probability sampling, namely saturated sampling. Collecting data using a questionnaire given to all respondents. Hypothesis testing in this study uses multiple linear regression analysis method. From the results of the research that has been carried out, it is found that the suitability of compensation, organizational commitment and organizational culture has a significant influence on distributive justice. From these results it can be concluded that the higher the level of suitability of compensation, organizational commitment and organizational culture, the level of distributive justice felt by employees will also increase.